IMPLEMENTASI MANAJEMEN RISIKO DALAM MENINGKATKAN MUTU PENDIDIKAN (PENELITIAN DI SMK Al-HADI BANDUNG) - Rahmawati , Irma; Hidayat , Wahyu (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
There are always risks in human life, be it in the activities of individuals, organizations, institutions, companies, or even goverments. As humans, we need to be careful and make the right calculations in everything because risks are usually considered as adverse events. Therefore, to always be able to face risks in various unpredictable situations, risk management is needed. Qualitative methods were used by the author to obtain data about the Al-Hadi Vocational School Curriculum through interviews and literature reviews. The aim of this research is to find out whether risk management can help Improve the quality of education at Al-Hadi Vocational School through the process of improving the quality of education. To improve the quality of education, risk management is very important to reduce risks that have occurred and will occur in educational institutions.